The biology and culture of pearl oyster (Bivalvia Pteriidae) - Gervis, M.H.; Sims, N.A. (Manila, Philippines ICLARM, 1992)
ICLARM Stud. Rev. 21
Keywords: Aquaculture techniques; Biology; Pearl oysters; Pearl culture